Guía de comunicación para el tercer sector: enfoques de patrocinio y mecenazgo - Sanchez Tucres, Yarixa Nicole (Machala, 2023)
This research work aims to develop a comprehensive guide to sponsorship and patronage for a non-profit organization, third sector, forming links with companies through social responsibility. In the first instance, the aim is to learn about sponsorship and patronage in order to understand what it is, how it arises and how they differ and to find out if both help to form a link between the third sector and companies. The methodology of this study adopts a qualitative approach. The data collection will include interviews for non-probabilistic samples: teachers of the Faculty of Business Sciences, CSR Executive Companies and CEO and Third sector, information that will contribute to the proposal, guide, dossier and sponsorship and sponsorship plan, which will be evaluated upon completion. The purpose of this study is to leave a contribution that will guide future academic works, where the implementation of patronage and sponsorship in the third sector is sought.
El presente trabajo de investigación tiene como objetivo desarrollar una guía integral de patrocinio y mecenazgo para una organización sin fin de lucro, tercer sector, formando vínculos con las empresas por medio de la responsabilidad social. En primera instancia, se pretende conocer sobre el mecenazgo y patrocinio para entender qué es, cómo surge, en qué se diferencian y encontrar si ambas ayudan a formar un vínculo entre el tercer sector y las empresas. La metodología de este estudio adopta un enfoque cualitativo. La recolección de datos incluirá entrevistas para muestras no probabilísticas: docentes de la Facultad de Ciencias Empresariales, Empresas Ejecutivos de RSC y CEO y Tercer sector, información que contribuirá en la propuesta, guía, dossier y plan de mecenazgo y patrocinio, que al finalizarlos serán evaluados. Este estudio tiene como finalidad dejar un aporte que guíe a futuros trabajos académicos, en donde se busque implementar el mecenazgo y patrocinio en un tercer sector.
Keywords: PATROCINIO; MECENAZGO; RESPONSABILIDAD SOCIAL CORPORATIVA; RELACIONES PUBLICAS; CULTURA; FUNDRAISING; CROWDFUNDING; FILANTROPIA; SPORINZACION; MARKETING; COMUNICACION; TERCER SECTOR.